The subthalamic nucleus at 7.0 Tesla: evaluation of sequence and orientation for deep-brain stimulation - Kerl, Hans Ulrich (Acta neurochirurgica, 2012)
BackgroundDeep-brain stimulation (DBS) of the subthalamic nucleus (STN) is an accepted neurosurgical technique for the treatment of medication-resistant Parkinson’s disease and other neurological disorders. The accurate targeting of the STN is facilitated by precise and reliable identification in pre-stereotactic magnetic resonance imaging (MRI).The aim of the study was to compare and evaluate different promising MRI methods at 7.0 T for the pre-stereotactic visualisation of the STNMethodsMRI (T2-turbo spin-echo [TSE], T1-gradient echo [GRE], fast low-angle shot [FLASH] two-dimensional [2D] T2* and susceptibility-weighted imaging [SWI]) was performed in nine healthy volunteers. Delineation and image quality for the STN were independently evaluated by two neuroradiologists using a six-point grading system. Inter-rater reliability, contrast-to-noise ratios (CNRs) and signal-to-noise ratios (SNRs) for the STN were calculated. For the anatomical validation, the coronal FLASH 2D T2* images were co-registered with a stereotactic atlas (Schaltenbrand-Wahren).ResultsThe STN was clearly and reliably visualised in FLASH 2D T2* imaging (particularly coronal view), with a sharp delineation between the STN, the substantia nigra and the zona incerta. No major artefacts in the STN were observed in any of the sequences. FLASH 2D T2* and SWI images offered significantly higher CNR for the STN compared with T2-TSE. The co-registration of the coronal FLASH 2D T2* images with the stereotactic atlas affirmed the correct localisation of the STN in all cases.ConclusionThe STN is best and reliably visualised in FLASH 2D T2* imaging (particularly coronal orientation) at 7.0-T MRI.